Essays on the nexus of climate change, agricultural productivity, and the environment - Ekong, Olabisi Aderonke (Kansas State University, 2021)
Agriculture is highly dependent on and sensitive to weather. Warming effects result from greenhouse gas emissions and aerosols from a small number of countries but its impact will be felt on a global scale. So far, agricultural productivity growth has sustained the continuous global supply of food but will this continue into the foreseeable future with the incidence of climate change? The effects of climate change on crop yields have been the focus of several studies. However, the sensitivity of agricultural productivity (measured as Total Factor Productivity-TFP) to climate change is not well understood. The first essay examines how historical changes in temperature and precipitation have affected the evolution of agricultural total factor productivity (TFP) while accounting for the short and long term impact. A fixed effect regression model for 128 countries for a period of 1961 to 2014 was employed to exploit yearly changes in temperature and precipitation as the identification strategy. Results show that precipitation has a significant effect on TFP growth in Sub-Saharan Africa, tropical and low income countries. Global short term temperature effect is offset in the long run showing that farmers adapt to reduce the effects of temperature in their behavioral decisions. Irrespective of the impact of climate change, there have been calls for an increase in agricultural productivity due to uncertainty and a global decline in Research and Development (R&D) expenditures. Previous literature accounts for the effect of global TFP growth on global food security and the environment. My second essay estimates the impact of TFP growth in different regions on global food security and the environment using a partial equilibrium model. To construct comparable TFP shocks across regions, I consider three TFP shock scenarios: (i) a uniform 100 percent increase in TFP growth in each region, (ii) TFP growth in each region that gives the same decrease in global commodity price, and (iii) TFP growth in each region resulting from the same increase in R&D expenditure. Results show that a 100% increase in TFP in the US & Canada increases agricultural carbon emission within the US & Canada by 16.9% but with a net global decrease in agricultural carbon emissions by 4.27%. In addition, a 100% increase in TFP in the US & Canada decreases global food security (malnutrition) by 13.09%. These results provide justification to support increasing R&D expenditures in developed regions. Overall, TFP growth is most effective in Sub-Saharan Africa as it gives the largest reductions in malnutrition and carbon emissions.
Keywords: Agricultural productivity; Total factor productivity (TFP); Climate change; Research and development (R&D); Food security (malnutrition); Carbon emission